Inorganic colloid spinning solution with high inorganic components and preparation method thereof

By preparing small-sized rubber sols at low hydrogen ion concentrations and large-sized rubber sols at high hydrogen ion concentrations, combined with ultrasonic assisted technology and microwave high-pressure concentration, the problem of high spinning agent content in the existing inorganic sol spinning liquid is solved, and the quality and performance of ceramic fibers are significantly improved.

CN118932527BActive Publication Date: 2025-03-28DONGHUA UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411182159.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-27
Publication Date
2025-03-28
Estimated Expiration
2044-08-27

AI Technical Summary

Technical Problem

The existing inorganic sol spinning liquid has a high content of spinning agent, which leads to a low content of inorganic components, affecting the quality and performance of ceramic fibers.

Method used

By preparing small-sized rubber sols with low polycondensation reaction activity at low hydrogen ion concentration, and preparing large-sized rubber sols with high polycondensation reaction activity at high hydrogen ion concentration, combined with ultrasonic assisted technology and microwave high-pressure concentration, an inorganic rubber spun liquid with high inorganic components was obtained.

Benefits of technology

The content of inorganic components is significantly improved, the quality and performance of ceramic fibers are improved, and the viscosity and conductivity of the spinning liquid are within a suitable range.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to an inorganic colloid spinning solution with high inorganic components and a preparation method thereof. The preparation method is specifically as follows: an inorganic sol of small-sized colloid particles with low polycondensation reaction activity is uniformly mixed and stirred with an inorganic sol of large-sized colloid particles capped with alkyl groups or alkoxy groups, and an ionic strength regulator is added, and then a low-molecular-weight non-rigid polymer is added for stirring, and the obtained polymer / inorganic colloid mixed solution is subjected to microwave-assisted high-pressure concentration, so that the solution is uniformly heated everywhere, the diffusion of the solvent is promoted, and the concentration of the low-molecular-weight polymer reaches an overlapping concentration, and a high-inorganic component inorganic colloid spinning solution with spinnability is obtained. Compared with the prior art, the inorganic component content in the inorganic colloid spinning solution prepared by the present invention is (20-70) wt%, the viscosity is (10-1000) mPa·s, and the conductivity is (100-15000) μS / cm; the metal alkoxide in the inorganic colloid spinning solution is one or more of a titanium source, a zirconium source, a zinc source, an aluminum source, and a silicon source, and has good universality.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of inorganic colloid particle spinning solution, in particular to an inorganic colloid particle spinning solution with high inorganic components and a preparation method thereof. Background Art

[0002] Ceramic fiber materials have the advantages of light weight, high temperature resistance, good thermal stability, excellent chemical stability and mechanical vibration resistance, so they have been widely used in all walks of life. Among them, the diameter of ceramic ultrafine fibers is one to two orders of magnitude lower than that of traditional micron fibers. Due to their unique morphological structure, they play a key functional material in the fields of aerospace, national defense and military industry, and play an irreplaceable role in improving industrial production efficiency and promoting scientific and technological progress. At present, the main preparation method of ceramic ultrafine fibers is a combination of sol-gel method and electrospinning method, that is, sol is formed by hydrolysis of alcohol salt, and then it is prepared into spinning solution with spinning aids, and then ceramic fibers with controllable diameter are obtained by electrospinning and high-temperature calcination. However, the content of spinning aids added to the existing inorganic sol spinning solution is relatively high, which makes the content of inorganic components in the spinning solution low, resulting in low conversion rate of hybrid fibers prepared by subsequent processes and difficulty in improving mechanical properties.

[0003] In view of the above problems, Chinese patent CN113944008B discloses a flexible and high-strength silica nanofiber membrane and its preparation method, which performs catalytic hydrolysis-condensation reaction by dropwise addition or slow injection of a catalyst aqueous solution, with the addition rate not exceeding 1wt% of the total amount of catalyst / aqueous solution per second, and the temperature is controlled below 20°C. After 30min-10h of stirring, an electrospinning solution with a solid content of more than 15wt% is prepared, and a flexible and high-strength silica nanofiber membrane is obtained. However, this method requires precise control of the catalyst drop rate and is not suitable for large-scale production. Chinese patent CN117534444B discloses an alumina ceramic nanofiber aerogel with a high solid content inorganic aluminum sol and a preparation method thereof, wherein the alumina ceramic nanofiber aerogel is prepared by dissolving an aluminum salt in deionized water, adding aluminum powder in different proportions, stirring evenly, and reacting the mixture at a high temperature in a water bath solution to obtain an inorganic aluminum sol with a high solid content. The inorganic aluminum sol obtained by the method has an alumina solid content of (15 to 30) wt%, and the degree of improvement in the solid content is still limited. Moreover, the method is only applicable to inorganic aluminum sols, and is not applicable to other inorganic sol spinning solutions, and is not universal.

[0004] In summary, there is an urgent need to develop a stable preparation method for inorganic colloid spinning solution with universal applicability and high inorganic content, so that the quality and performance of ceramic fibers prepared in subsequent processes can be effectively improved. Summary of the invention

[0005] The purpose of the present invention is to provide an inorganic colloid spinning solution with high inorganic components and a preparation method thereof in order to overcome the defects of the above-mentioned prior art. The metal alkoxide in the prepared inorganic colloid spinning solution is one or more of a titanium source, a zirconium source, a zinc source, an aluminum source, and a silicon source, and has good universality.

[0006] The purpose of the present invention can be achieved by the following technical solutions:

[0007] The present invention provides a method for preparing an inorganic colloid spinning solution with a high inorganic component content, comprising the following steps:

[0008] S1: Mixing metal alkoxide, deionized water, solvent and catalyst to prepare homogeneous sol, adding chelating agent at low hydrogen ion concentration to obtain inorganic sol with small-sized colloidal particles with low polycondensation reaction activity;

[0009] S2: mixing metal alkoxide, deionized water, solvent and catalyst to prepare homogeneous sol, adding silane coupling agent at high hydrogen ion concentration to obtain inorganic sol with large-sized colloidal particles terminated with alkyl groups or alkoxy groups;

[0010] S3: Under low temperature, the inorganic sol of small-sized colloid particles in S1 and the inorganic sol of large-sized colloid particles in S2 are uniformly mixed and stirred, and an ionic strength regulator is added to promote the formation of a solvation layer in the sol and inhibit the aggregation of inorganic colloid particles, thereby obtaining a thermodynamically balanced dual-sized colloid composite sol driven by entropy;

[0011] S4: A low molecular weight non-rigid polymer is added to the dual-size colloidal particle composite sol obtained in S3 and stirred. After the polymer chain segments and the colloidal particles are adsorbed to each other, the movable stretching part of the molecular chain is shorter and less prone to entanglement. Compared with long molecular chains, it has a higher space utilization rate and adsorbs more colloidal particles to obtain a polymer / inorganic colloidal particle mixed solution;

[0012] S5: The polymer / inorganic colloid mixture obtained in S4 is subjected to microwave-assisted high-pressure concentration to uniformly heat the solution, promote the diffusion of the solvent, and make the concentration of the low molecular weight polymer reach the overlapping concentration, so as to obtain a high inorganic component inorganic colloid spinning solution with spinnability.

[0013] In one embodiment of the present invention, in S1, the molar ratio of the metal alkoxide, deionized water, solvent, and catalyst is 1:(0-20):(0-20):(0.001-15), wherein deionized water and solvent are selected at the same time or one of them is selected;

[0014] The low hydrogen ion concentration range is (0.001-0.1) mol·L -1 Preferably, the low hydrogen ion concentration range is (0.003~0.01)mol·L-1 ;

[0015] In S2, the molar ratio of the metal alkoxide, deionized water, solvent, and catalyst is 1:(0-20):(0-20):(0.001-15), and the high hydrogen ion concentration range is (0.1-5) mol·L -1 Preferably, the high hydrogen ion concentration range is (0.15-0.9) mol·L -1 ; Among them, deionized water and solvent are selected at the same time or one of them is selected.

[0016] In one embodiment of the present invention, the titanium source is one or more of isopropyl titanate, butyl titanate, titanium n-propoxide, titanium isopropoxide, titanium n-butoxide, titanium isobutoxide, and titanium n-octoxide;

[0017] The zirconium source is one or more of zirconium n-propoxide, zirconium isopropoxide, zirconium n-butoxide, zirconium isobutoxide, and zirconium n-octoxide;

[0018] The zinc source is one or more of zinc n-propoxide, zinc isopropoxide, zinc n-butoxide, zinc isobutoxide, and zinc n-octoxide;

[0019] The aluminum source is one or more of aluminum isopropoxide, aluminum n-butoxide, aluminum isobutoxide, aluminum n-propoxide, and aluminum ethoxide;

[0020] The silicon source is one or more of tetraethyl orthosilicate, tetra-n-propoxysilane, tetraethoxysilane, and methyltriethoxysilane.

[0021] In one embodiment of the present invention,

[0022] In S1 and S2, the metal alkoxide is one or more of a titanium source, a zirconium source, a zinc source, an aluminum source, and a silicon source; the solvent is one or more of methanol, ethanol, isopropanol, butanol, pentanol, hexanol, ethylene glycol, propylene glycol, benzyl alcohol, allyl alcohol, and octanol; the catalyst is one or more of oxalic acid, acetic acid, phosphoric acid, hydrofluoric acid, and trifluoroacetic acid; the chelating agent is one or more of acetylacetone, citric acid, amino alcohol, ethylenediaminetetraacetic acid, sodium gluconate, sodium citrate, and sodium tartrate;

[0023] In S2, the silane coupling agent is one or more of γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, γ-glycidyloxypropyltrimethoxysilane, methyltriethoxysilane, methyltrimethoxysilane, vinyltrimethoxysilane, phenyltrimethoxysilane, vinyltriethoxysilane, phenyltriethoxysilane, γ-methacryloxypropyltrimethoxysilane, trichloropropylsilane, vinyltri(β-methoxyethoxy)silane, and trichloroethoxysilane.

[0024] In one embodiment of the present invention, in S1, the particle size of the small-sized colloid particles is less than or equal to 20 nm, the reaction temperature is (10-60)°C, the stirring speed is (50-5000) rpm, and the reaction time is (1-12) h; preferably, the reaction temperature is (20-30)°C, the stirring speed is (500-2000) rpm, and the reaction time is (5-10) h.

[0025] In S2, the particle size of the large-size colloid particles is greater than or equal to 30 nm, the reaction temperature is 10-60°C, the stirring speed is (50-5000) rpm, and the reaction time is (1-16) h; preferably, the reaction temperature is (20-30)°C, the stirring speed is (500-2000) rpm, and the reaction time is (8-10) h.

[0026] In one embodiment of the present invention, in S3, the ionic strength regulator is one or more of sodium chloride, potassium chloride, sodium nitrate, sodium bicarbonate, sodium sulfate, magnesium sulfate, sodium hydroxide, potassium hydroxide, hydrochloric acid, sulfuric acid, nitric acid, aluminum sulfate, ferric sulfate, sodium acetate, potassium aluminum sulfate, acetic acid-sodium acetate buffer, phosphate buffer, citric acid-citrate buffer, Tris buffer, HEPES buffer, MES buffer, glucose, sucrose, and glycerol;

[0027] The reaction temperature is (1-15)°C, the ultrasonic frequency is (20-40) kHz, the stirring speed is (50-5000) rpm, and the reaction time is (1-10) h; preferably, the reaction temperature is (5-10)°C, the stirring speed is (800-1600) rpm, and the reaction time is (6-8) h.

[0028] In one embodiment of the present invention, in S4, the non-rigid polymer is one or more of polyvinyl alcohol, hydroxypropyl methylcellulose, polyethylene oxide, polyvinyl pyrrolidone, polyacrylonitrile, polylactic acid, and polymethyl methacrylate;

[0029] The molecular weight of the non-rigid polymer is (1-30) W, and the proportion of the non-rigid polymer in the spinning solution is (0.1-5) wt%;

[0030] The reaction temperature is (1-40)°C, the stirring speed is (50-5000) rpm, and the reaction time is (1-12) h; preferably, the reaction time is (4-6) h, the reaction temperature is (25-30)°C, and the stirring speed is (500-1000) rpm.

[0031] Further, in S5, the microwave frequency is (300-30000) MHz, and the reaction pressure is (100-6000) kPa; preferably, the microwave frequency is (300-650) MHz, and the reaction pressure is (200-700) kPa;

[0032] The invention also provides an inorganic colloid spinning solution with high inorganic components.

[0033] In one embodiment of the present invention, the inorganic component content in the inorganic colloid spinning solution is (20-70) wt%, the viscosity is (10-1000) mPa·s, and the conductivity is (100-15000) μS / cm; preferably, the inorganic component content in the inorganic colloid spinning solution is 28-60 wt%, the viscosity is (230-600) mPa·s, and the conductivity is (450-12800) μS / cm.

[0034] The present invention obtains an inorganic sol with low polycondensation reaction activity under low hydrogen ion concentration, and further reduces the hydrolysis and polycondensation rate of alcohol salt by adding a chelating agent, thereby greatly slowing down the nucleation rate in the sol, and the chelating group coordinates with the metal atom to form a shielding effect, thereby inhibiting the aggregation and further growth of the colloid particles, thereby obtaining a uniform small-sized colloid particle sol. Under high hydrogen ion concentration conditions, an inorganic sol with high polycondensation reaction activity is obtained, the colloid nucleus grows rapidly, and large-sized colloid particles are formed. The silane coupling agent provides an alkyl group or an alkoxy group to end-cap the large-sized colloid particles, thereby preventing the large-sized colloid particles from continuing to undergo polycondensation reaction. At the same time, due to the increase in the protonation degree of the colloid particles, a large number of anions in the solution are adsorbed on the central metal atom that is positively charged after being protonated, thereby forming an anion adsorption layer, and free cations are adsorbed on the periphery of the anions to form a counterion adsorption layer, and the obtained double electric layer structure inhibits the degree of polycondensation reaction, thereby obtaining stable large-sized inorganic colloid particles.

[0035] The present invention prepares a dual-size colloidal particle sol by ultrasound-assisted technical means under a low-temperature environment. First, the two-size mixed sol is pretreated by low-power ultrasound to prevent the colloidal particles from agglomerating under the direct action of high power. The temperature of the reaction system is controlled by an ice bath to reduce the impact of temperature rise due to the input of ultrasonic energy and avoid the occurrence of gelation caused by excessive polycondensation caused by high temperature. At the same time, an ionic strength regulator is added to change the ion concentration in the solution, promote the solvation layer to become thicker and more stable, provide steric hindrance and electrostatic repulsion, prevent the aggregation of inorganic colloidal particles, and obtain a thermodynamically stable dual-size colloidal particle composite sol driven by entropy.

[0036] A low molecular weight non-rigid polymer is introduced into the dual-size colloid compound sol to improve the spinnability of the inorganic sol. After the polymer chain segments and the colloid particles are adsorbed on each other, the movable and stretchable part of the molecular chain is shorter and less prone to entanglement. Compared with long molecular chains, it has a higher space utilization rate and can adsorb more colloid particles, thereby obtaining a polymer-assisted inorganic sol. In order to improve the spinnability of the inorganic colloid spinning solution, the solution is subjected to microwave-assisted high-pressure concentration. The action of microwaves and high pressure causes the solution to be evenly heated throughout, promotes the diffusion of the solvent, and makes the concentration of the low molecular weight polymer reach an overlapping concentration, thereby obtaining a spinnable inorganic colloid spinning solution with a high inorganic component.

[0037] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0038] 1. The inorganic component content in the inorganic colloid spinning solution prepared in the present invention is (20-70) wt%, which significantly increases the content of the inorganic component. The viscosity of the prepared inorganic colloid spinning solution is (10-1000) mPa·s, and the conductivity is (100-15000) μS / cm.

[0039] 2. The metal alkoxide in the inorganic colloid spinning solution prepared in the present invention is one or more of a titanium source, a zirconium source, a zinc source, an aluminum source, and a silicon source, and has good universality. DETAILED DESCRIPTION

[0040] The specific implementation methods of the present invention are described in detail below through examples. These examples are implemented on the premise of the scheme described in the present invention, and provide detailed implementation methods and specific operating processes, but the protection scope of the present invention is not limited to the following examples.

[0041] The present invention is further described below in conjunction with specific embodiments. Any features such as component models, material names, connection structures, preparation methods, materials, structures or composition ratios not clearly described in this technical solution are deemed to be common technical features disclosed in the prior art.

[0042] Example 1

[0043] This embodiment provides a method for preparing an inorganic colloid spinning solution with a high inorganic component, comprising the following steps:

[0044] S1: Tetraethoxysilane, deionized water, and phosphoric acid were uniformly mixed in a molar ratio of 1:11:0.02. The hydrogen ion concentration in the solution was 0.027 mol·L -1 , and then add acetylacetone to obtain an inorganic sol of small-sized colloid particles with low polycondensation reaction activity. The particle size of the small-sized colloid particles is (6-10) nm, the reaction temperature is 25° C., the stirring speed is 500 rpm, and the reaction time is 8 hours;

[0045] S2: Tetraethoxysilane, deionized water, and phosphoric acid were uniformly mixed in a molar ratio of 1:11:0.3, and the hydrogen ion concentration in the solution was 0.4 mol·L -1 , then methyltriethoxysilane was added to obtain an inorganic sol having large-sized colloid particles terminated with alkoxy groups, wherein the particle size of the large-sized colloid particles was (40-50) nm, the reaction temperature was 25° C., the stirring speed was 1000 rpm, and the reaction time was 8 h;

[0046] S3: Under 10°C, the two different sizes of colloid particles in S1 and S2 were ultrasonically dispersed and mixed for 6 hours. The ultrasonic frequency was gradually increased to 28kHz to make the sols of colloid particles of different sizes evenly mixed. The stirring speed was 800rpm. At the same time, phosphate buffer was added to promote the formation of the solvation layer in the sol and prevent the aggregation of inorganic colloid particles. A thermodynamically stable dual-size colloid composite sol was obtained under entropy driving;

[0047] S4: Adding polyvinyl pyrrolidone with a molecular weight of 10W and an addition amount of 3wt% to the dual-size colloidal particle composite sol in S3, the reaction temperature is 28°C, the rotation speed is 500rpm, and the polymer-inorganic colloidal particle spinning solution is obtained after fully mixing for 4 hours;

[0048] S5: The polymer-inorganic colloid spinning solution obtained in S4 is concentrated by microwave at 200 kPa, and the microwave frequency is gradually increased to 300 MHz. After the solution viscosity reaches 230 mPa·s, it is collected to obtain an inorganic colloid spinning solution with an inorganic component content of 28 wt%.

[0049] This embodiment also provides an inorganic colloid spinning solution with a high inorganic component, wherein the inorganic colloid spinning solution has a conductivity of 450 μS / cm, a viscosity of 230 mPa·s, and an inorganic component content of 28 wt%. The conductivity is tested using the standard "GB / T 11007-2008 Conductivity Meter Test Method". The viscosity is tested using the "rotation method" in the standard "GB / T 10247-2008 Viscosity Test Method".

[0050] Example 2

[0051] This embodiment provides a method for preparing an inorganic colloid spinning solution with a high inorganic component, comprising the following steps:

[0052] S1: Titanium butyl, deionized water, ethanol, and acetic acid were uniformly mixed in a molar ratio of 1:3.25:18:6.25 to obtain a hydrogen ion concentration of 0.093 mol·L -1, adding ethylenediaminetetraacetic acid to obtain an inorganic sol of small-sized colloid particles with low polycondensation reaction activity, wherein the particle size of the small-sized colloid particles is (4-8) nm, the reaction temperature is 20° C., the stirring speed is 800 rpm, and the reaction time is 6 hours;

[0053] S2: Titanate butyl, deionized water, ethanol, and acetic acid were uniformly mixed in a molar ratio of 1:3.25:13:10, and the hydrogen ion concentration was 0.15 mol·L -1 , then adding methyltriethoxysilane to obtain an inorganic sol having large-sized colloid particles terminated with alkoxy groups, wherein the particle size of the large-sized colloid particles is (30-40) nm, the reaction temperature is 20° C., the stirring speed is 1200 rpm, and the reaction time is 10 h;

[0054] S3: At 5°C, the small-sized colloid particles in S1 and the large-sized colloid particles in S2 were ultrasonically dispersed and mixed for 8 hours. The ultrasonic frequency was gradually increased to 40kHz to uniformly mix the sols of colloid particles of different sizes. The stirring speed was 1000rpm. At the same time, acetic acid-sodium acetate buffer was added to promote the formation of a solvation layer in the sol and prevent the aggregation of inorganic colloid particles. A thermodynamically stable dual-sized colloid composite sol was obtained under entropy driving.

[0055] S4: Adding polyvinyl alcohol with a molecular weight of 4W and an addition amount of 3.3wt% to the dual-size colloidal particle composite sol in S3, the reaction temperature is 30°C, the rotation speed is 600rpm, and the polymer-inorganic colloidal particle spinning solution is obtained after fully mixing for 5 hours;

[0056] S5: The polymer-inorganic colloid spinning solution in S4 is concentrated by microwave at 500 kPa, and the microwave frequency is gradually increased to 650 MHz. After the solution viscosity reaches 400 mPa·s, it is collected to obtain an inorganic colloid spinning solution with an inorganic component content of 60 wt%.

[0057] This embodiment also provides an inorganic colloid spinning solution with a high inorganic component, wherein the conductivity of the inorganic colloid spinning solution is 7000 μS / cm, the viscosity is 400 mPa·s, and the inorganic component content accounts for 60 wt%. The conductivity is tested using the standard "GB / T 11007-2008 Conductivity Meter Test Method". The viscosity is tested using the "rotation method" in the standard "GB / T 10247-2008 Viscosity Test Method".

[0058] Example 3

[0059] This embodiment provides an inorganic colloid spinning solution with a high inorganic component, comprising the following steps:

[0060] S1: zirconium n-propoxide, deionized water, ethanol, and acetic acid were uniformly mixed in a molar ratio of 1:0.5:10:1.5. The hydrogen ion concentration in the solution was 0.042 mol·L -1 , and then add amino alcohol to obtain an inorganic sol with small-sized particles of low polycondensation reaction activity, wherein the reaction temperature of the small-sized particles (10-15) nm is 28° C., the stirring condition is 500 rpm, and the reaction time is 8 hours;

[0061] S2: zirconium n-propoxide, deionized water, ethanol, and acetic acid were uniformly mixed in a molar ratio of 1:17:10:8.5. The hydrogen ion concentration in the solution was 0.147 mol·L -1 , and then adding γ-aminopropyltriethoxysilane to obtain an inorganic sol having large-sized colloid particles terminated with alkoxy groups, wherein the particle size of the large-sized colloid particles is (60-70) nm, the reaction temperature is 28° C., the stirring speed is 500 rpm, and the reaction time is 8 hours;

[0062] S3: Under 8°C, the inorganic sol of small-sized colloid particles in S1 and the inorganic sol of large-sized colloid particles in S2 were ultrasonically dispersed and mixed for 6 hours. The ultrasonic frequency was gradually increased to 30kHz to uniformly mix the two sols of colloid particles of different sizes. The stirring condition was 1200rpm. At the same time, acetic acid-sodium acetate buffer was added to promote the formation of a solvation layer in the sol and prevent the aggregation of inorganic colloid particles. A thermodynamically stable dual-sized colloid composite sol was obtained under entropy driving.

[0063] S4: Adding polyethylene oxide with a molecular weight of 10W and an addition amount of 0.8 wt% to the dual-size colloidal particle composite sol obtained in S3, the reaction temperature is 25°C, the rotation speed is 550 rpm, and the polymer-inorganic colloidal particle spinning solution is obtained after fully mixing for 6 hours;

[0064] S5: The polymer-inorganic colloid spinning solution obtained in S4 is concentrated by microwave at 700 kPa, and the microwave frequency is gradually increased to 500 MHz. After the solution viscosity reaches 300 mPa·s, it is collected to obtain an inorganic colloid spinning solution with an inorganic component content of 60 wt%.

[0065] This embodiment also provides an inorganic colloid spinning solution with a high inorganic component, wherein the conductivity of the inorganic colloid spinning solution is 1000 μS / cm, the viscosity is 300 mPa·s, and the inorganic component content accounts for 60 wt%. The conductivity is tested using the standard "GB / T 11007-2008 Conductivity Meter Test Method". The viscosity is measured using the "rotation method" in the standard "GB / T 10247-2008 Viscosity Test Method".

[0066] Example 4

[0067] This embodiment provides a method for preparing an inorganic colloid spinning solution with a high inorganic component, comprising the following steps:

[0068] S1: Titanium isopropyl, ethanol and acetic acid were uniformly mixed in a molar ratio of 1:19.7:0.25, and the hydrogen ion concentration in the solution was 0.003 mol·L -1 , and then adding sodium citrate to obtain an inorganic sol of small-sized colloid particles with low polycondensation reaction activity, wherein the particle size of the small-sized colloid particles is (4-10) nm, the reaction temperature is 25° C., the stirring speed is 2000 rpm, and the reaction time is 6 hours;

[0069] S2: Titanium isopropyl, ethanol, and acetic acid were uniformly mixed in a molar ratio of 1:19.7:8.75, and the hydrogen ion concentration in the solution was 0.129 mol·L -1 , and then adding vinyl triethoxysilane to obtain an inorganic sol having large-sized colloid particles terminated with alkoxy groups, wherein the particle size of the large-sized colloid particles is (30-35) nm, the reaction temperature is 25° C., the stirring speed is 2000 rpm, and the reaction time is 10 h;

[0070] S3: Under 5°C, the inorganic sol of small-sized colloid particles in S1 and the inorganic sol of large-sized colloid particles in S2 were ultrasonically dispersed and mixed for 8 hours. The ultrasonic frequency was gradually increased to 30kHz to evenly mix the two sols of colloid particles of different sizes. The stirring speed was 1000rpm. At the same time, acetic acid-sodium acetate buffer was added to promote the formation of a solvation layer in the sol and prevent the aggregation of inorganic colloid particles. A thermodynamically stable dual-sized colloid composite sol was obtained under entropy driving;

[0071] S4: Add 4 wt% hydroxypropyl methylcellulose with a molecular weight of 30W to the dual-size colloidal particle composite sol in S3, the reaction temperature is 20°C, the rotation speed is 800 rpm, and the polymer-inorganic colloidal particle spinning solution is obtained after sufficient mixing for 4 hours;

[0072] S5: The polymer-inorganic colloid spinning solution obtained in S4 is concentrated by microwave at 500 kPa, and the microwave frequency is gradually increased to 400 MHz. After the solution viscosity reaches 400 mPa·s, it is collected to obtain an inorganic colloid spinning solution with an inorganic component content of 60 wt%.

[0073] This embodiment also provides an inorganic colloid spinning solution with a high inorganic component, wherein the conductivity of the inorganic colloid spinning solution is 1200 μS / cm, the solution viscosity is 400 mPa·s, and the inorganic component content accounts for 60 wt%. The conductivity is tested using the standard "GB / T 11007-2008 Conductivity Meter Test Method". The viscosity is measured using the "rotation method" in the standard "GB / T 10247-2008 Viscosity Test Method".

[0074] Example 5

[0075] This embodiment provides a method for preparing an inorganic colloid spinning solution with a high inorganic component, comprising the following steps:

[0076] S1: Tetraethyl orthosilicate, deionized water, ethanol, and oxalic acid were uniformly mixed in a molar ratio of 1:0.71:3.57:0.016. The hydrogen ion concentration in the solution was 0.046 mol·L -1 , adding acetylacetone to obtain an inorganic sol of small-sized colloid particles with low polycondensation reaction activity, wherein the particle size of the small-sized colloid particles is (8-15) nm, the reaction temperature is 20° C., the stirring speed is 1800 rpm, and the reaction time is 5 hours;

[0077] S2: Tetraethyl orthosilicate, deionized water, ethanol, and oxalic acid were uniformly mixed in a molar ratio of 1:0.71:3.57:0.07. The hydrogen ion concentration in the solution was 0.202 mol·L -1 , and then adding vinyl triethoxysilane to obtain an inorganic sol having large-sized colloid particles terminated with alkoxy groups, wherein the particle size of the large-sized colloid particles is 30 to 40 nm, the reaction temperature is 20° C., the stirring speed is 2000 rpm, and the reaction time is 10 h;

[0078] S3: Under 5°C, the inorganic sol of small-sized colloid particles in S1 and the inorganic sol of large-sized colloid particles in S2 were ultrasonically dispersed and mixed for 8 hours. The ultrasonic frequency was gradually increased to 30kHz to uniformly mix the two sols of colloid particles of different sizes. The stirring speed was 1200rpm. At the same time, acetic acid-sodium acetate buffer was added to promote the formation of a solvation layer in the sol and prevent the aggregation of inorganic colloid particles. A thermodynamically stable dual-sized colloid composite sol was obtained under entropy driving;

[0079] S4: Add hydroxypropyl methylcellulose with a molecular weight of 1W and an addition ratio of 4wt% to the dual-size colloidal particle composite sol in S3, the reaction temperature is 25°C, the rotation speed is 1000rpm, and the polymer-inorganic colloidal particle spinning solution is obtained after sufficient mixing for 4h;

[0080] S5: The polymer-inorganic colloid spinning solution obtained in S4 is concentrated by microwave at 400 kPa, and the microwave frequency is gradually increased to 500 MHz. After the solution viscosity reaches 600 mPa·s, it is collected to obtain an inorganic colloid spinning solution with an inorganic component content of 60 wt%.

[0081] This embodiment also provides an inorganic colloid spinning solution with a high inorganic component, wherein the conductivity of the inorganic colloid spinning solution is 5000 μS / cm, the solution viscosity is 600 mPa·s, and the inorganic component content accounts for 60 wt%. The conductivity is tested using the standard "GB / T 11007-2008 Conductivity Meter Test Method". The viscosity is measured using the "rotation method" in the standard "GB / T 10247-2008 Viscosity Test Method".

[0082] Example 6

[0083] This embodiment provides a method for preparing an inorganic colloid spinning solution with a high inorganic component, comprising the following steps:

[0084] S1: Tetraethyl orthosilicate, deionized water, and oxalic acid were uniformly mixed in a molar ratio of 1:8.1:0.018. The hydrogen ion concentration in the solution was 0.062 mol·L -1 , adding citric acid to obtain an inorganic sol of small-sized colloid particles with low polycondensation reaction activity, wherein the particle size of the small-sized colloid particles is (10-18) nm, the reaction temperature is 30° C., the stirring speed is 2000 rpm, and the reaction time is 10 h;

[0085] S2: Tetraethyl orthosilicate, deionized water, and oxalic acid were uniformly mixed in a molar ratio of 1:8.1:0.25. The hydrogen ion concentration in the solution was 0.892 mol·L -1 , then adding methyltrimethoxysilane to obtain an inorganic sol having large-sized colloid particles terminated with alkoxy groups, wherein the particle size of the large-sized colloid particles is (50-60) nm, the reaction temperature is 30° C., the stirring speed is 2000 rpm, and the reaction time is 10 h;

[0086] S3: Under 5°C, the inorganic sol of small-sized colloid particles in S1 and the inorganic sol of large-sized colloid particles in S2 were ultrasonically dispersed and mixed for 8 hours. The ultrasonic frequency was gradually increased to 25kHz to uniformly mix the two sols of colloid particles of different sizes. The stirring condition was 1600rpm. At the same time, sodium chloride solution was added to promote the formation of a solvation layer in the sol and prevent the aggregation of inorganic colloid particles. A thermodynamically stable dual-sized colloid composite sol was obtained under entropy driving.

[0087] S4: Add polyvinyl alcohol with a molecular weight of 2W and an addition ratio of 3wt% to the dual-size colloidal particle composite sol in S3, the reaction temperature is 25°C, the rotation speed is 700rpm, and the polymer-inorganic colloidal particle spinning solution is obtained after sufficient mixing for 6 hours;

[0088] S5: The polymer-inorganic colloid spinning solution obtained in S4 is concentrated by microwave at 300 kPa, and the microwave frequency is gradually increased to 400 MHz. After the solution viscosity reaches 450 mPa·s, it is collected to obtain an inorganic colloid spinning solution with an inorganic component content of 50 wt%. The conductivity is tested using the standard "GB / T 11007-2008 Conductivity Meter Test Method". The viscosity is measured using the "rotation method" in the standard "GB / T 10247-2008 Viscosity Test Method".

[0089] This embodiment also provides an inorganic colloid spinning solution with a high inorganic component, wherein the conductivity of the inorganic colloid spinning solution is 12800 μS / cm, the solution viscosity is 450 mPa·s, and the content of the inorganic component accounts for 50 wt%.

[0090] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A method for preparing an inorganic colloid spinning solution with a high inorganic component, characterized in that: The following steps are involved: S1: Mixing metal alkoxide, deionized water, solvent and catalyst to prepare homogeneous sol, adding chelating agent under low hydrogen ion concentration range to obtain inorganic sol with small-sized colloidal particles with low polycondensation reaction activity; S2: mixing metal alkoxide, deionized water, solvent and catalyst to prepare homogeneous sol, adding silane coupling agent under high hydrogen ion concentration range to obtain inorganic sol with large-sized colloidal particles terminated with alkyl groups or alkoxy groups; S3: Under low temperature conditions, the inorganic sol of small-sized colloid particles in S1 and the inorganic sol of large-sized colloid particles in S2 are uniformly mixed and stirred, and an ionic strength regulator is added to promote the formation of a solvation layer in the sol, inhibit the aggregation of inorganic colloid particles, and obtain a thermodynamically balanced dual-sized colloid particle composite sol; S4: A low molecular weight non-rigid polymer is added to the dual-size colloidal particle composite sol obtained in S3 and stirred. After the polymer chain segments and the colloidal particles are adsorbed to each other, the movable stretching part of the molecular chain is shorter and less prone to entanglement. Compared with the long molecular chain, it has a higher space utilization rate and adsorbs more colloidal particles to obtain a polymer-inorganic colloidal particle mixed solution; S5: subjecting the polymer / inorganic colloid mixed solution obtained in S4 to microwave-assisted high-pressure concentration, so that the solution is evenly heated, the diffusion of the solvent is promoted, and the concentration of the low molecular weight polymer reaches an overlapping concentration, thereby obtaining a high inorganic component inorganic colloid spinning solution with spinnability; In S1, the low hydrogen ion concentration is greater than or equal to 0.001 mol·L -1 And less than or equal to 0.1 mol·L -1 The molar ratio of the metal alkoxide, deionized water, solvent and catalyst is 1:(0-20):(0-20):(0.001-15), wherein deionized water and solvent are selected at the same time or one of them is selected; In S2, the high hydrogen ion concentration is greater than 0.1 mol·L -1 And less than or equal to 5 mol·L -1 The molar ratio of the metal alkoxide, deionized water, solvent and catalyst is 1:(0-20):(0-20):(0.001-15), wherein deionized water and solvent are selected at the same time or one of them is selected; In S3, the reaction temperature of the low temperature environment is (1~15)℃; In S4, the non-rigid polymer is one or more of polyvinyl alcohol, hydroxypropyl methylcellulose, polyethylene oxide, polyvinyl pyrrolidone, polyacrylonitrile, polylactic acid, and polymethyl methacrylate; and the molecular weight of the non-rigid polymer is (1~30)W.

2. The method for preparing a high-inorganic-component inorganic colloid spinning solution according to claim 1, characterized in that: In S1 and S2, the metal alkoxide is one or more of a titanium source, a zirconium source, a zinc source, an aluminum source, and a silicon source; the solvent is one or more of methanol, ethanol, isopropanol, butanol, pentanol, hexanol, ethylene glycol, propylene glycol, benzyl alcohol, allyl alcohol, and octanol; the catalyst is one or more of oxalic acid, acetic acid, phosphoric acid, hydrofluoric acid, and trifluoroacetic acid; the chelating agent is one or more of acetylacetone, citric acid, amino alcohol, ethylenediaminetetraacetic acid, sodium gluconate, sodium citrate, and sodium tartrate; In S2, the silane coupling agent is one or more of γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, γ-glycidyloxypropyltrimethoxysilane, methyltriethoxysilane, methyltrimethoxysilane, vinyltrimethoxysilane, phenyltrimethoxysilane, vinyltriethoxysilane, phenyltriethoxysilane, γ-methacryloxypropyltrimethoxysilane, trichloropropylsilane, vinyltri(β-methoxyethoxy)silane, and trichloroethoxysilane.

3. The method for preparing a high-inorganic-component inorganic colloid spinning solution according to claim 2, characterized in that: The titanium source is one or more of isopropyl titanate, butyl titanate, titanium n-propoxide, titanium isopropoxide, titanium n-butoxide, titanium isobutoxide, and titanium n-octoxide; The zirconium source is one or more of zirconium n-propoxide, zirconium isopropoxide, zirconium n-butoxide, zirconium isobutoxide, and zirconium n-octoxide; The zinc source is one or more of zinc n-propoxide, zinc isopropoxide, zinc n-butoxide, zinc isobutoxide, and zinc n-octoxide; The aluminum source is one or more of aluminum isopropoxide, aluminum n-butoxide, aluminum isobutoxide, aluminum n-propoxide, and aluminum ethoxide; The silicon source is one or more of tetraethyl orthosilicate, tetra-n-propoxysilane, tetraethoxysilane, and methyltriethoxysilane.

4. The method for preparing a high-inorganic-component inorganic colloid spinning solution according to claim 1, characterized in that: In S1, the particle size of the small-sized colloid particles is less than or equal to 20 nm, the reaction temperature is (10-60) °C, the stirring speed is (50-5000) rpm, and the reaction time is (1-12) h; In S2, the particle size of the large-size colloid particles is greater than or equal to 30 nm, the reaction temperature is (10-60)°C, the stirring speed is (50-5000) rpm, and the reaction time is (50-5000) h.

5. The method for preparing a high-inorganic-component inorganic colloid spinning solution according to claim 1, characterized in that: In S3, the ionic strength regulator is one or more of sodium chloride, potassium chloride, sodium nitrate, sodium bicarbonate, sodium sulfate, magnesium sulfate, sodium hydroxide, potassium hydroxide, hydrochloric acid, sulfuric acid, nitric acid, aluminum sulfate, ferric sulfate, sodium acetate, potassium aluminum sulfate, acetic acid-sodium acetate buffer, phosphate buffer, citric acid-citrate buffer, Tris buffer, HEPES buffer, MES buffer, glucose, sucrose, and glycerol; The ultrasonic frequency is (20~40) kHz, the stirring speed is (50~5000) rpm, and the reaction time is (1~10) h.

6. The method for preparing a high-inorganic-component inorganic colloid spinning solution according to claim 1, characterized in that: In S4, the proportion of non-rigid polymer in the spinning solution is (0.1~5) wt%; The reaction temperature is (1~40)°C, the stirring speed is (50~5000) rpm, and the reaction time is (1~12) h.

7. The method for preparing a high-inorganic-component inorganic colloid spinning solution according to claim 1, characterized in that: In S5, the microwave frequency is (300-30000) MHz, and the reaction pressure is (100-6000) kPa.

8. An inorganic colloid spinning solution with high inorganic content obtained by the preparation method as described in any one of claims 1 to 7.

9. The inorganic colloid spinning solution with high inorganic content according to claim 8, characterized in that: The inorganic component content in the inorganic colloid spinning solution is (20-70) wt%, the viscosity is (10-1000) mPa·s, and the conductivity is (100-15000) μS / cm.

Citation Information

Patent Citations

  • A flexible, high-strength silica nanofiber membrane and its preparation method

    CN113944008B

  • Alumina ceramic nanofiber aerogel with high solid content inorganic aluminum sol and preparation method thereof

    CN117534444B

  • Inorganic nanoparticle dispersion for high-transparency high-barrier polyester material, and preparation method thereof

    CN103205091A

  • Flexible metal hydroxide nanofiber material as well as preparation method and application thereof

    CN114369885A